Evaluasi Digitalisasi Webdesaku di Desa Sawahkulon - Harry Mulya Zein; Aqli Hayat Tribrata; Rizaldy Izzulhaq; Andreas Tarigan; Muhammad Jilan Alfari; Rizky Nur Azizah; Novia Annisa Kusworo Putri; Coby Bryan Weya; Sisca Septiani (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
With the rapid development of information technology, this study was carried out to evaluate the implementation and utilization of WEBDESAKU in the context of the Sawahkulon Village government. The research method used is qualitative, with data collection techniques through observation, documentation, and literature studies. The results show that WEBDESAKU is essential in transforming village governance improving effectiveness, transparency, and accountability. However, there are obstacles related to community understanding and awareness and the capabilities of village equipment in operating this platform. However, concerning Purwakarta Regent Regulation Number 253 of 2019, this study highlights the potential of WEBDESAKU as a vital instrument in implementing technology-based governance in Sawahkulon Village.